Comparison of the induction of neutralizing antibodies against Bas congo virus using several vaccine modalities - Park, Eun-Sil; Yoshikawa, Tomoki; Tani, Hideki; Kimura, Masanobu; Kaku, Yoshihiro; Imaoka, Koichi; Maeda, Ken; Saijo, Masayuki; Morikawa, Shigeru (Scientific reports, 2025)
The Bas-Congo virus (BASV) is a novel rhabdovirus that causes viral hemorrhagic fever in 2009. Since BASV has not been isolated, there is limited information on BASV, and potential therapeutics or vaccines have not yet been developed. In the present study, we used the synthetic cDNA of the BASV-G protein to develop 4 different types of vaccine, using a recombinant BASV-G protein, a plasmid DNA that expresses the BASV-G protein, a recombinant vaccinia virus that expresses the BASV-G protein, and a pseudotype virus based on hydrogen peroxide-inactivated vesicular stomatitis virus (VSV) that expresses the BASV-G protein (BASVpv). BASVpv was generated and used for the evaluation of neutralizing antibodies and the induction of virus neutralizing antibody upon inoculation (BASVpv/GFP) of these candidates in rabbits. The results showed that both the recombinant vaccinia virus and the hydrogen peroxide-inactivated VLPs effectively induced neutralizing antibodies, even with a single inoculation.